Customer feedback online : case studies of Swedish manufacturing SMEs - Opoku, Robert Ankomah; Khan, Muhammad Naeem (2004)
Keeping existing customers as well as attracting new ones have been a critical concern to many firms. Collecting and monitoring customer feedback online in these regard have given firms the possibility to assess and upgrade their services and product capabilities as needed to maintain and improve competitiveness. This thesis aims at exploring and describing the tools used by SMEs to collect customer feedback online, their components and the criteria used in selecting these Internet-based tools. The research is deductive and qualitative. Multiple in-depth case studies were conducted on three SMEs in Luleå, Norrbotten region of Sweden all of which are engaged in customer feedback collection online. Documentation and personal interviews were used. The data collected was analysed in a cross-case analysis. Based on a threefold purpose and a conceptual framework, we concluded that e-mail is the most dominant tool though supported by other online tools. These tools are also supplemented with other offline means such as questionnaire, telephone and focus group meetings. Components of an internet-based customer feedback system and the criteria for assessing an Internet-based customer feedback collection tool also were identified. Validerat; 20101217 (root)